Magang Guru Tamu DKV Mata Pelajaran Dasar-Dasar Program Keahlian SMK Multistudi High School - Ramadhan, Said Teguh (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Internasional Batam, 2023)
Abstract This study aims to explain and analyze the internship experience as a guest teacher majoring in Visual Communication Design (DKV) at Multistudi High School Vocational High School. Visiting teacher internships are activities that provide opportunities for professional practitioners to share their knowledge and experiences with students. In addition, visiting teacher internships also provide benefits for writers to be able to broaden their professional network and gain new perspectives on the latest developments in the world of teaching. This research concludes that the internship activities for guest teachers majoring in DKV at Multistudi High School Vocational Schools have significant value in enriching the writer's learning experience and increasing soft skill and hard skill competence. Recommendations for further research are to further evaluate the long-term effects of this guest teacher internship and to dig deeper into the specific aspects that provide the most significant benefits to students and teachers at SMK Multistudi High School. Keywords: Apprenticeship, DKV, Competence, Soft Skills, Hard Skills.